Aspectos históricos e empíricos dos temas do teste das fábulas - Souza, Rodrigo Luís Bispo (2013)
This Masters Degree Dissertation is divided in two parts: the first section is a review of the literature and the second one is an empirical work, according to the norms of the Post Graduation Program in Psychology of the Pontificia Universidade Católica do Ro Grande do Sul. The first study, whose title is The development of the themes in the Fables test , aimed to review works on the Fables test which have also been dedicated to the study of the themes and to the changes in the test throughout its evolution. A review of the literature has been carried out through an asymmetric review with critical analyses of the data. The analysed works vary from 1946 to 1993 and are discussed considering its contributions both to the development of the themes and to the instrument. Moreover, gaps and limitations are pointed out. The second study, Accordance between judges for the themes of the Fables test , searched to discover if the themes proposed by Cunha e Nunes (1993) are present in the verbalizations of a sample of students. It is an observational, descriptive and transversal study. 104 protocol of verbalization of the Fables test which, along with an evaluation card for the subjects, were read and evaluated separately by pairs of judges. For the analysis of the data it was used the calculation of Kappa with its frequency adjusted to all the fables. The results point to the necessity of better definitions of the themes offered by the test